Validity and Reliability of Marathi Version of Edinburgh Postnatal Depression Scale as a Screening Tool for Post Natal Depression - Khapre, Meenakshi; Dhande, Nikhil; Mudey, Abhay (National Journal of Community Medicine, 2017)
Context: The prevalence of Post natal depression in India ranges from 12 – 23 %. It has substantial impact on mother, father, family and thereby cognitive and emotional development of child. Therefore the post natal depression screening should be given foremost importance. The Edinburgh Postnatal Depression Scale (EPDS) is a reliable tool used in many countries. The study conducted to validate the Marathi version of EPDS Method: All the mothers with history of delivery in last six months but not less than six weeks were included in study. Linguistically validated Questionnaire was posed by interviewer and recorded. To test the reliability, mothers were revisited after a period of 2 weeks to administer same questionnaire and assessed by expert. Statistical analysis: SPSS 17 was used to know the floor and ceiling effect, exploratory factor analysis, receiver and operating curve, cronbach’s alpha, intraclass correlation coefficient. Result: Total mean score was 10.3 ± 4.1. No floor and ceiling effect seen. Three factors were extracted. Best cut off point was 12 with 95 % sensitivity and specificity. Depression was associated with birth of female child, pregnancy complications and health of newborn. Conclusion: The findings of study indicates that Marathi version of EPDS has good validity, internal consistency and adequate reliability.